Studies on Eumastacoid grasshoppers: Paralethus montanus n. sp. (Orthoptera: Episactidae) from Chiapas, Mexico - Cadena-Castañeda, Oscar J.; Chamé-Vázquez, Eduardo Rafael (Zootaxa, 2024)
Paralethus montanus n. sp. is described from Chiapas, Mexico. This new species constitutes the first record of the genus for Mexico, previously known only for El Salvador and Guatemala, and it is the first episactid species collected at higher elevations (above 3000 m). A standardization for the abbreviations of the genital structures of episactids is proposed, which could apply to other groups of eumastacoids. A key for the identification of Paralethus species is also provided. Finally, the taxonomy of the genus and the spatial and altitudinal distribution of Central American taxa are discussed.